Effects of caffeine on the metabolism of rats exercising by swimming - Denadai, B. S. [UNESP] (My University, 1994)
Several studies have demonstrated that caffeine improves endurance exercise performance but the mechanisms are not fully understood. Possibilities include increased free fatty acid (FFA) oxidation with consequent sparing of muscle glycogen as well as enhancement of neuromuscular function during exercise. The present study was designed to investigate the effects of caffeine on liver and muscle glycogen of 3-month old, male Wistar rats (250-300 g) exercising by swimming. Caffeine (5 mg/kg) dissolved in saline (CAF) or 0.9% sodium chloride (SAL) was administered by oral intubation (1 μl/g) to fed rats 60 min before exercise. The rats (N=8-10 per group) swam bearing a load corresponding to 5% body weight for 30 or 60 min. FFA levels were significantly elevated to 0.475±0.10 mEq/l in CAF compared to 0.369±0.06 mEq/l in SAL rats at the beginning of exercise. During exercise, a significant difference in FFA levels between CAF and SAL rats was observed at 30 min (0.325±0.06 vs 0.274±0.05 mEq/l) but not at 60 min (0.424±0.13 vs 0.385±0.10 mEq/l). Blood glucose showed an increase due to caffeine only at the end of exercise (CAF=142.1±27.4 and SAL=120.2±12.9 mg/100 ml). No significant difference in liver or muscle glycogen was observed in CAF as compared to SAL rats, at rest or during exercise. Caffeine increased blood lactate only at the beginning of exercise (CAF=2.13±0.2 and SAL=1.78±0.2 mmol/l). These data indicate that caffeine (5 mg/kg) has no glycogen-sparing effect on rats exercising by swimming even though the FFA levels of CAF rats were significantly higher at the beginning of exercise.
Keywords: caffeine; exercise; free fatty acids; muscle glycogen